Respostas

2014-03-20T14:51:07-03:00
5x + 3y= 22
8x + 5y= 36

5x + 3y= 22   * (-8/5)

8x + 5y= 36  

-8x – 4,8y= -35,2  
8x + 5y= 36
     

   – 4,8y= -35,2
         5y= 36      
      0,2y= 0,8
           
          y= 4

5x + 3y = 22

5x + 12 = 22        
5x = 10
         
x = 2

----------------------------------------------------------

5x + 7y= 1
3x - 4y= 2

-5x + 7y= 1 * (3/5)
3x - 4y= 2  

-3x + 4,2y= 0,6
3x - 4y= 2  

4,2y= 0,6  
- 4y= 2

0,2y= 2,6     
y=13

-5x + 7y = 1

-5x + 91 = 1
-5x = -90 *(-1)  
 5x = 90
  
   x = 18